Generalization Of $ω$-Closed Sets via Operators and Ideals - Carpintero, C.; Rosas, E.; Salas, M.; Sanabria, J.; Vàsquez, L. (Sarajevo Journal of Mathematics, 2024)
A new type of closed sets in a topological space, called $ω_{\mathcal{I}, γ}$-closed sets, is introduced and studied. Also we studied and characterized the class of spaces having $(\mathcal{I}, γ)$-tightness. 2010 Mathematics Subject Classification. 54C10, 54D10